CNTM-03. Functional connectivity networks in patients with brain tumors and vascular lesions in the occipital cortex. (12th November 2021) - Rosengarth, Katharina; Hense, Katharina; Plank, Tina; Greenlee, Mark; Wendl, Christina; Proescholdt, Martin; Schmidt, Nils-Ole
Abstract: OBJECTIVE: Space-occupying brain lesions as brain tumors in the occipital lobe have only been sparsely investigated so far, as this localization is extremely rare with only 1% of cases. It is still unclear how this affects the overall organization of the visual system. We investigated functional connectivity of functional networks associated with higher visual processing between patients with occipital space-occupying lesion in the occipital cortex and healthy controls. METHODS: 12 patients with brain tumors, 7 patients with vascular lesions in the occipital cortex and 19 healthy subjects matched for age and sex were included. During functional MRI patients and subjects performed a visual excentricity mapping task. Data analysis was done using CONN toolbox based on Matlab. See-to-ROI connectivities of 23 Regions of Interest (ROIs) implemented in the CONN toolbox which were assigned to the Default Mode, Visual, Salience, Dorsal Attention, and Frontoparietal network were assessed. For each subject, connectivity was calculated using Fischer transformed pairwise correlations. These correlations were first considered separately for each group in one-sample analyses and then compared between the groups. RESULTS: Main results show, that compared to control subjects and vascular patients, tumor patients showed weaker intra-network connectivity of components of all networks except the default-network. Tumor patients showed even stronger between-network connectivity in the default-mode network compared to the other groups. Weaker connectivity was observed within the salience network in both patient groups compared to controls. CONCLUSION: The results indicate that in the course of the disease, compensatory countermeasures take place in the brain against a brain tumor or a space-occupying brain lesion with the aim of maintaining the performance level and cognitive processes for as long as possible. However, more research is needed in this area to understand the mechanisms and effects of brain tumors and space-consuming brain lesions on surrounding tissue.